Indústrias criativas: Festival de Cultura e Gastronomia de Tiradentes/Minas Gerais/Brasil - Furtado, Silvana Mello (2015)
The objective of the research was to analyze the Festival of Culture and Gastronomy of Tiradentes, in the state of Minas Gerais, Brazil, and correlate it to the National Gastronomy Festival of Santarém, Portugal, and the Conventual Sweets Festival of Alcobaça, also in Portugal; and also insert it in the context of the debate on creative industries, with emphasis on cuisine - here conceived in their economic, cultural and creative dimensions. The work is the result of a scholarship at the University of Coimbra, in Portugal, sponsored by CAPES (Higher Education & Personnel Training Coordination), to account for the relations between the Portuguese cuisine and the gastronomic production of Brazil; for this, the above festivals on Portuguese gastronomy were analyzed. The adopted methodological procedures were constituted of a secondary research carried out through bibliographic survey, and an exploratory-qualitative primary research, involving collection of information and an analysis of the field under study, together with an ethnographic observation through the application of twenty-two interviews with residents and owners of restaurants and hotels, in the town of Tiradentes, plus the information collected in interviews and festivals of Santarém and Alcobaça, Portugal; a case study of qualitative fragment was also part, in which the social unit and the social event were both investigated, with their respective demonstrations and agents. Pierre Bourdieu and Michel de Certeau were fundamental authors for the understanding of gastronomy and the arts of cooking. The Portuguese influence and its representation in the gastronomic culture of Brazil are very present in the dialogue with authors like Gilberto Freyre, Câmara Cascudo, Ricardo Miranda, Claudia Maria Lima e Ivonne Hamilton. To elaborate on "creative industries" all the research conducted by the United Nations Conference on Trade and Development (UNCTAD) and the Federation of Industries of the State of Rio de Janeiro (FIRJAN) for the classification of creative segments, with emphasis on gastronomy and the role of the creative and cultural economy in the socioeconomic development of cities, were of basic importance; as well as the report with recommendations by the United Nations Organization (UNO)